We going to calculate this limit just putting the value of the limit in place of x:

`lim(x->2) (x^3-8)/(x-2) = (8-8)/(2-2) =>` `lim(x->2) (x^3-8)/(x-2) = 0/0`

The limit didn't work so we will try factoring.

By factoring (`x^3-8` ) in `(x - 2)(x^2+4x+4)` we get:

`lim(x->2) (x - 2)(x^2+4x+4)/(x - 2) = lim(x->2) (x^2+4x+4)`

We will put the value of the limit in place of x:

`lim(x->2) (x^2+4x+4)= 16`

**Your answer is `lim(x->2) (x^3-8)/(x-2) = 16.`**

## See eNotes Ad-Free

Start your **48-hour free trial** to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Already a member? Log in here.